Direct amplification of casework samples in fabrics using GlobalFiler® PCR Amplification Kit. (December 2015) - Brito, P.; Gouveia, N.; Bogas, V.; Serra, A.; Balsa, F.; Andrade, L.; São-Bento, M.; Cunha, P.; Lopes, V.; Anjos, M.J.
Abstract: After a validation study developed in the Forensics Genetic and Biology Service of Coimbra, Portugal, we were able to demonstrate the ability of the GlobalFiler ® PCR Amplification kit in direct amplification of reference samples with consistent and reproducible results. Since this kit is optimized for casework samples, we decided to test it on forensic samples, in particular on fabrics stains. The selected samples had already been processed according to the methodologies normally used for this type of samples included automated extraction, quantification and amplification, followed by capillary electrophoresis, resulting in complete profiles. To develop our study, samples were collected from regions of the fabrics that had previously shown/proven to have biological evidence. The chosen samples were directly amplified for the GlobalFiler ® PCR Amplification kit, followed by capillary electrophoresis on the ABI PRISM ® 3500 Genetic Analyzer. The results obtained with this methodology revealed full and well balanced genetic profiles. This study intends to show that in some cases this approach can be an alternative, when we are in the presence of biological stains on fabrics, that allows to obtain consistent results in a short period of time.